Wertheim-Meigs radical hysterectomy - Carvalho, Jesus Paula (1994)
Wertheim-Meigs hysterectomy is the treatment of choice for invasive cervix cancer stage IB and IIA at the University of São Paulo Medical School. It was performed in 168 patients between 1974 and 1993. Pelvic lymph node metastases were found in 19 patients (11.3%) and 149 were negative lymph node. The recurrence rate was 21% in the positive lymph node and 6% in the negative lymph node patients. Complications occurred in 35 patients (20.83%) and were as follows: atonic bladder in 9.52%; fistulae in 5.59%; urinary incontinence in 4.76%; ureteral stenosis in 2.97%; dehiscence in 2.38% and lymphedema in 1.19%. Intraoperative complications occurred at a rate of 4.76% and involved injuries to the bladder, ureter and great vessels.